Comparing Paper and Digital Assignments: Effects on Secondary Students’ Writing Accuracy and Fluency - Hutagalung, Teguh; E, Yon A; Solo, Lenny (Universitas Pahlawan Tuanku Tambusai, 2025)
With the growing integration of digital tools in education, there is a need to understand how the medium of assignment delivery influences students’ writing development. The research involved two groups of students who were assigned writing tasks using paper and digital platforms. Writing samples were evaluated based on coherence, grammar, vocabulary usage, and organization. Results indicated that digital-based assignments demonstrated significantly greater improvement in students' writing skills, particularly in vocabulary usage, organization, and revision efficiency. The average post-test scores of Digital Group (23–24 out of 25) were higher than the Paper-based group (22–23 out of 25), with an effect size ranging from Cohen’s d = 1.100 to 1.108, indicating a large educational impact. In the Descriptive Writing section, the results indicate that the mean and standard deviation for the paper-based group are 18.09 (SD = 1.446) for the pre-test and 21.18 (SD = 1.079) for the post-test. In contrast, the digital-based group shows a mean of 16.73 (SD = 1.272) for the pre-test and 22.64 (SD = 1.120) for the post-test. In the Argumentative Writing section, the results reveal that the mean and standard deviation for the paper-based group are 17.09 (SD = 1.446) for the pre-test and 22.07 (SD = 1.536) for the post-test, whereas the digital-based group has a mean of 19.00 (SD = 1.539) for the pre-test and 23.85 (SD = 1.453) for the post-test. Based on these results, it is evident that the most significant improvements were observed in the digital-based group, which showed an increase of 5.91 points in Descriptive Writing and 4.85 points in Argumentative Writing assignments. However, paper-based tasks were more effective in promoting deeper planning and reducing distractions. The study concludes that a blended approach may offer the most balanced benefit in developing students’ writing competencies.